Community Development, Creativity and Tourism in Creating Social Welfare: Case Study of Saung Angklung Udjo, Bandung, West Java - Musthofa, B M (KnE Social Sciences, 2018)
Abstract Community development, creativity and tourism can complement each other. All of these can synergize through the creation of an environment conducive and fulfilling the needs of the wider society. This article is the result of a qualitative research that discusses the strategy of community development, creativity and tourism in Saung Angklung Udjo (SAU). Saung Angklung Udjo (SAU) is a conducive place that is deliberately created by Udjo (the founder) to support the activities of the community development and tourism by developing creativity in culture and art traditions. The results show that Udjo’s strategy in community development activities is heavily based on the elements of local culture and traditional values of Sunda. Furthermore, the strength of Udjo Ngalagena as the SAU founder and the activities of community development in collaborating with tourism industry are the key to success for SAU to improve the quality of life and welfare of their community. Keywords: community development, creativity, tourism, traditions, angklung